A leucistic female Canis latrans(Carnivora: Canidae) in Costa Rica - Corrales-Gutiérrez, Daniel (EUNED, 2019)
Hembra de Canis latrans (Carnivora: Canidae) in Costa Rica". La despigmentación parcial (leucismo) es poco común en mamíferos. Aquí reportamos un total de 17 registros fotográficos de una hembra leucística de coyote (Canis latrans) en Costa Rica entre 2014 y 2018. The coyote (Canis latrans) is a canid with a geographic distribution ranging from Alaska to western Panama (Wainwright, 2007). In Costa Rica, it is associated with both open (e.g. dry forest, paramo), and disturbed habitats (e.g. agricultural lands, areas near small towns) and primarily at elevations below 3 400m (Wainwright, 2007; Wilson & Mittermeier, 2009). Coyote coloration ranges from gray to rufous, with darker and grayer col-orations more common at higher latitudes (Bekoff, 1977; Wilson & Mittermeier, 2009). Melanistic coyotes are rare (Gipson, 1976; Wilson & Mittermeier, 2009) while albino and leucistic (e.g. partially depigmented) coyote reports are even scarcer (Johnston, 1930; Young, 1951; López-González, 2011). Herein, we document the first evidence of a leucistic coyote in Costa Rica.